Craftsmanship in the structure of social-cultural life of Bukhara - Kahramonovna, Dzhomardova Dilafruz (Middle European Scientific Bulletin, 2021)
. The article deals with the formation and development of handicraft shops in the structure of the socio-cultural life of Bukhara. The structure and socio-cultural significance of the craft organizations of the workshop of painters, ornamentalists, masters of artistic products is considered. It shows the education of the apprentice (apprentice) in the master in the shop of painters, based on the life rules of artisans (rice). Turning to the history of the issue, the author notes the diversity of the types and forms of the creations of the painters of the workshop of painters who contributed to the enrichment of the folk art of Central Asia. The abundance and diversity of the socio-cultural life of Uzbeks and Tajiks confirm the continuity of the traditions of the schools of craft organizations. The statute in the form of legends outlined the history of the craft and regulated the duties of members of craft shops. The author summarizes that the treatises regulate the labor - professional life of artisan shops, cementing ethical canons in relation to the worker. It was believed that the craft received from a good master, does not know adversity, even if the student is deprived of all of his wealth. For the craft is inexhaustible, as a source.